The Principals’ and Teacher Counsellors’ Perception of the Factors Influencing Effective Delivery of Guidance and Conselling Services in Public Secondary Schools in Laikipia District - Karangu, Githua N.; Kathuri, Nephat J; Muola, James Muthee (International Association of African Researchers, 2011)
Despite the institutionalization of guidance and counselling programme in Kenyan public secondary schools, cases of indiscipline are still rampant. This study investigated the factors that influence the delivery of effective guidance and counselling services in all the 45 public secondary schools in Laikipia District as perceived by school principals and teacher counsellors. Two questionnaires, one for principals and another for teacher counselors provided data which was analysed using descriptive statistics and t-test. The findings showed that there is no significant difference in the perception of the effect of training, experience, workload, age and gender of the teacher counsellors and students’ attitudes on delivery of guidance and counselling between the principals and teacher counsellors. There is a statistically significant (P < 0.05, t = -2.115) difference in the perception of the effect of availability of facilities on delivery of guidance and counselling services between the principals and teacher counsellors. It was concluded that, although principals and teacher counsellors understood what is required for effective counselling, they have not done much to ensure the success of the programme. In order to have effective delivery of guidance and counselling services, there is need to provide sufficient facilities and training for teacher counsellors.